Fever-Associated Supraventricular Tachycardia after 4CMenB Vaccination in an Infant - Erdem Gönüllü; Burcu Topçu; Naci Öner; Ahmet Soysal; Metin Karaböcüoğlu (Case Reports in Pediatrics)
Meningococcal serogroup B vaccine 4CMenB (Bexsero) is a new four-component protein vaccine developed to prevent Neisseria meningitidis serogroup B infections. Case. We report a girl with fever and supraventricular tachycardia (SVT) 6–8 hours after the second dose of 4CMenB. SVT was unresponsive to the first dose of adenosine but terminated after the fourth dose of adenosine. During three months of follow-up, she was free of further SVT attacks. Conclusion. This is the first report of ECG-proven SVT after 4CMenB vaccination. Even if fever is coexistent, SVT should be considered after persistent tachycardia and 4CMenB vaccination.